2020
DOI: 10.1111/1754-9485.13082
|View full text |Cite
|
Sign up to set email alerts
|

Chemical shift imaging in the identification of those renal tumours that contain microscopic fat and the utility of multiparametric MRI in their differentiation

Abstract: Introduction: The aim of this study was to assess the qualitative and MRI findings of renal tumours, to determine which lesions contain microscopic fat, one of the potential differentiating factors between tumour types. Methods: 73 patients who underwent 3 Tesla MRI including chemical shift imaging, with subsequent biopsy or excision for histopathological diagnosis, were included in the study. The images were reviewed for a decrease in signal intensity (SI) on the opposed phase compared with the in-phase gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, these imaging features also apply to RCC. In previous studies, a signal intensity decrease was observed in 60%-80% of clear cell RCC due to its intracellular lipid[ 10 , 11 ]. Other than clear cell RCC, microscopic fat is also found in fat-poor angiomyolipoma (AML), papillary RCC, chromophobe RCC, and oncocytoma [11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these imaging features also apply to RCC. In previous studies, a signal intensity decrease was observed in 60%-80% of clear cell RCC due to its intracellular lipid[ 10 , 11 ]. Other than clear cell RCC, microscopic fat is also found in fat-poor angiomyolipoma (AML), papillary RCC, chromophobe RCC, and oncocytoma [11] .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, a signal intensity decrease was observed in 60%-80% of clear cell RCC due to its intracellular lipid[ 10 , 11 ]. Other than clear cell RCC, microscopic fat is also found in fat-poor angiomyolipoma (AML), papillary RCC, chromophobe RCC, and oncocytoma [11] . Macroscopic fat is found in classic AML, Wilms tumor [12] , and rarely in RCC [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been reported cases of RCC with significant fat density, with few exceptions they have also had calcification- so if both macroscopic fat and calcification are present the lesion should be presumed to be malignant and treated accordingly [ 11 , 13 ]. Several studies have shown the presence of microscopic fat in a lesion most commonly occurs in AMLs and clear cell RCCs (60%) and is rarely seen in oncocytomas [ 4 , 14 , 15 ]. Contrast enhancement is then assessed in the corticomedullary phase.…”
Section: Discussionmentioning
confidence: 99%
“…Papillary RCCs usually show low SI relative to renal cortex on T2, as is the case with lipid poor AMLs, which do not contain any macroscopic fat and will appear low SI due to the abundance of smooth muscle [ 5 , 6 , 18 , 19 ]. They can often be differentiated as lipid poor AMLs commonly contain microscopic fat, significantly more often than in papillary RCCs [ 4 , 14 , 15 ]. Our working group also established that the mean CSI for lipid poor AMLs was 73%, significantly higher than any other renal tumour type [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical shift imaging is based on differences in the inherent magnetic field experienced by the protons in fat molecules in comparison to those in the molecules of water, which are caused by the effects of the non-proton components of the molecules (carbon versus oxygen, respectively) on the electron cloud that surrounds the protons [4,5].…”
Section: Introductionmentioning
confidence: 99%